2014
DOI: 10.1155/2014/846570
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spinal, Inhalation, and Total Intravenous Anesthetic Techniques on Ischemia-Reperfusion Injury in Arthroscopic Knee Surgery

Abstract: Purpose. To compare the effects of different anesthesia techniques on tourniquet-related ischemia-reperfusion by measuring the levels of malondialdehyde (MDA), ischemia-modified albumin (IMA) and neuromuscular side effects. Methods. Sixty ASAI-II patients undergoing arthroscopic knee surgery were randomised to three groups. In Group S, intrathecal anesthesia was administered using levobupivacaine. Anesthesia was induced and maintained with sevoflurane in Group I and TIVA with propofol in Group T. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…These results might be due to the study design (spinal anesthesia, and good cardiovascular conditions with EF ≥ 55%). Koşucu et al [15] reported that total intravenous anesthesia with propofol could be better compared to inhalational anesthesia or spinal anesthesia, which were not signi cant. Their study with shorter duration of tourniquet application with 64-68 minutes is different from our study with 92-93 minutes of tourniquet application.…”
Section: Discussionmentioning
confidence: 97%
“…These results might be due to the study design (spinal anesthesia, and good cardiovascular conditions with EF ≥ 55%). Koşucu et al [15] reported that total intravenous anesthesia with propofol could be better compared to inhalational anesthesia or spinal anesthesia, which were not signi cant. Their study with shorter duration of tourniquet application with 64-68 minutes is different from our study with 92-93 minutes of tourniquet application.…”
Section: Discussionmentioning
confidence: 97%
“…Reperfusion of ischemic tissue results in potentially harmful pathophysiological reactions, such as production of oxygen free radicals which are released into the circulation after tourniquet deflation causing cellular injuries involving lipids, proteins & DNA leading to increase in serum potassium and lactate levels [10]. Some studies showed less hemodynamic and metabolic changes resulted from tourniquet application in patients undergoing regional anesthesia compared with general anesthesia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-operative and directly post-operative tourniquet pain (using "Wong-baker faces") in the three study groups. Kosucu et al [10] assessed the reperfusion injury of the arterial tourniquet on 60 patients underwent knee surgeries and divided into 3 groups received spinal anesthesia (S group), sevoflurane for induction and Maintenance (I group), and the third group received propofol for total intravenous anesthesia (T group).…”
Section: Discussionmentioning
confidence: 99%
“…Poor postoperative analgesia may effect mobilization, duration of discharge, patient satisfaction, morbidity and mortality. The studies evaluating the effects of regional anesthesia (RA) on functional outcome after TKA were conducted [35][36][37][38][39]. The results of some studies have suggested that Regional anesthesia seems to improve the outcome of patients undergoing total hip or knee replacement when compared with general anesthesia [36].…”
Section: Knee Surgerymentioning
confidence: 99%